A infecção pré-natal pelo Zika virus em camundongos imunocompetentes é associada com anormalidades da prole adulta - Vidyleison Neves Camargos (2020)
Zika virus (ZIKV) infection is associated with serious birth defects, including microcephaly, sensory, articular and muscle abnormalities, among others, which are defined as Congenital Zika Syndrome. Several infections during pregnancy are associated with the development of neuropsychiatric disorders secondary to changes in the neurodevelopmental process. However, neuropsychiatric consequences in the offspring born to ZIKV-infected dams are still unknown. Here, using an immunocompetent C57BL/6 mouse model, we performed an in-depth characterization of the effects of congenital ZIKV infection in the early stages of pregnancy until adulthood of offspring born to infected dams. For that, mouse pregnant dams were inoculated with 1x106 PFU/mouse of ZIKV by intraperitoneal route on the embryonic day 5.5 in the presence or absence of anti-envelope pan-flavivirus monoclonal antibody 4G2 to evaluate the phenomenon of antibody-dependent enhancement (ADE). Our results revealed that ZIKV induced maternal immune activation (MIA), which was associated with the occurrence of fetal alterations and death. Importantly, therapeutic administration of antiviral peptide AH-D during the early stages of pregnancy prevented ZIKV replication and reduced death of offspring. During the post-natal period, congenital ZIKV infection was associated with a reduction in whole brain volume, ophthalmological abnormalities, changes in the testicular morphology, and disruption in bone microarchitecture. Some alterations were enhanced in the presence of 4G2 antibody. Moreover, neuropathological alterations induced by ZIKV did not reflect on behavioral abnormalities in the male adult offspring, even when subjected to a second environmental hit during the peripubertal period. Overall, our results revealed that early maternal ZIKV infection causes several birth defects in immunocompetent mice, which can be potentiated by the ADE phenomenon and are associated with MIA. Additionally, antiviral treatment with AH-D peptide may be beneficial during early maternal ZIKV infection.